The Revitalization of The Madrasah Principal Leadership in Improving The Quality of Education - Herman, Herman; Kurniawan, Ade; Hasnadi, Hasnadi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to analyze the strategy of revitalizing the leadership of madrasah principals in improving the quality of education units in Madrasah Tsanawiyah (MTs) in the West Aceh Regency. This study uses a qualitative approach to revealing the factual conditions of the revitalization of madrasah leadership in improving the quality of education. Data collection techniques were carried out through observation, interviews, and document studies on reports of madrasa activities. Data analysis techniques for research results are carried out by interpreting and designing action plans on research results. The results show that the head of MTs West Aceh has not optimally improved the quality of functions in revitalizing the synergy and harmony among teachers and employees in improving the quality of education units, revitalizing processes, tools, and learning media in improving the quality of education units and revitalizing the participation of the community and government in improving quality. Education units in madrasas. The implication of the less than the optimal revitalization of madrasah leadership has resulted in a decline in the quality of the learning process and the quality of educational outcomes in madrasas.